MEDICAL STUDENTS' ATTITUDE TOWARDS HEALTH - SAVING TECHNOLOGIES AND HEALTHY LIFESTYLE - Haydarov N.K; Eshmurotov S.G. (Scholar Express Journals, 2025)
The article presents the results of a sociological survey of students of medical universities, using the example of the Bukhara State Medical Institute (BSMI) and the Tashkent State Dental Institute (TSDI). The analysis of the students' responses allowed us to conclude that not all students have an idea of health-saving technologies, there is no particular interest in issues of a healthy lifestyle (HLS). A certain pattern was revealed in the respondents' responses, the motivation to lead a healthy lifestyle increases dynamically with the transition to subsequent courses of study. Apparently, this is due to the acquisition of relevant knowledge on valeology, hygiene and health-saving factors in clinical disciplines that students take in older courses of study
Keywords: Students; Health; Lifestyle; Risk Factors